The minor allele rs2295613(A), protective against systemic lupus erythematosus, makes a differential contribution to the activity of the SLAMF1 gene promoter in T helpers and in regulatory T lymphocytes - A. N. Uvarova; L. V. Putlyaeva; E. A. Zheremyan; E. M. Stasevich; M. M. Murashko; E. A. Bogomolova; K. V. Korneev; D. E. Demin; A. M. Schwartz; D. V. Kuprash (Медицинская иммунология, 2025)
SLAMF1 (CD150) is a receptor expressed on various hematopoietic cells and involved in the pathogenesis of autoimmune diseases such as systemic lupus erythematosus (SLE). This disorder is a chronic autoimmune inflammatory disease characterized by dysregulation of B lymphocytes, production of a large number of autoantibodies, and various abnormalities in immune regulation, such as changes in the number and functions of T helper cells and T regulatory (Treg) lymphocytes. Expression of SLAMF1 on T helper cells and B lymphocytes is increased in patients with active SLE. Impaired interaction of SLAMF1 receptors on T and B lymphocytes reduces the production of IL-6 and differentiation of plasmablasts in SLE. In the present work, we performed a functional analysis of single nucleotide promoter polymorphisms rs2295614(A>T) and rs2295613(G>A) of the SLAMF1 gene in the models of T-regulatory lymphocytes (MT-2 cell line) and T helpers (Jurkat cell line). Previously, an association of the rs2295614(A)/rs2295613(G) haplotype with the risk of developing SLE was shown, and it was also demonstrated that the risk haplotype in the promoter region of the SLAMF1 gene increases promoter activity in the Jurkat T cell line. Using reporter analysis, we have shown that the activity of the SLAMF1 promoter containing the minor variant rs2295613(A) increases in MT-2 cells and decreases in Jurkat cells. Based on the analysis of transcriptomes of these cell lines, we suggest that such a differential effect of the protective minor rs2295613(A) variant on promoter activity may be mediated by differential binding of transcription factors: activating MYC/MAX heterodimer in MT-2 cells and repressor MAX/MXD4 in Jurkat cells. Furthermore, both the increased expression of SLAMF1 in regulatory T cells and its decreased expression in T helper cells are likely to impact SLE pathogenesis similarly. These changes could reduce the efficiency of activating signal transmission from T helper cells to B lymphocytes, thereby weakening the autoreactive response of B lymphocytes. Thus, we propose a molecular mechanism mediating the protective role of the minor rs2295613(A) allele in the development of SLE.